Indonesia 2020 : sebuah sketsa tentang visi & strategi dalam kepemimpinan manajemen politik dan ekonomi - Dwidjowijoto, Riant Nugroho, 1966- (Jakarta, Indonesia : RBI, 1998)
Indonesian politics, economy, etc. toward the year 2020; collected articles
Includes bibliographical references (p. 200-202) and index
Keywords: Indonesia -- Politics and overnment -- 1966- -- Forecasting; Indonesia -- Economic conditions -- 1945- -- Forecasting